Diagnostic accuracy of the 10/66 dementia assessment tool in Māori, Fijian‐Indian, Samoan and Tongan elders with memory problems living in South Auckland, New Zealand: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Martinez‐Ruiz, Adrian; Yates, Susan; Cheung, Gary; Dudley, Makarena Diana; Krishnamurthi, Rita; Fa'alau, Fuafiva; Roberts, Mary; Taufa, Seini; Fa'alili, Jacinta; Kerse, Ngaire; Cullum, Sarah
Abstract: Background: New Zealand is a multicultural multilingual country which brings challenges if we aim to conduct a dementia prevalence study that is representative of the whole of NZ population. The 10/66 dementia assessment tool was developed for use in non‐English speaking communities in order to accurately measure the prevalence of dementia. It is a language‐fair, culture‐fair questionnaire used in epidemiological studies of dementia. It has been translated and adapted into a culturally fair instrument for use with Māori, Fijian‐Indian, Samoan and Tongan elders living in New Zealand (NZ). Method: The translated and adapted 10/66 instrument versions were administered in the selected ethnicities. The results of the 10/66 dementia assessment it´s been tested in older people with and without dementia who have received a "gold standard" assessment in a local memory service in South Auckland. Each ethnic group included 15 subjects with dementia and 15 subjects without dementia. Result: Data is still being collected and analysed. The results will be presented at the conference, however the preliminary results for both Māori and Fijian‐Indian communities showed that the 10/66 dementia assessment has a sensitivity and specificity above 85%. Conclusion: We will test a culturally appropriate and scientifically rigorous method to calculate the prevalence of dementia in an inter‐ethnic community that includes Māori, Fijian‐Indian, Samoan and Tongan elders living in NZ. The information from this study can be used by the Ministry of Health to direct relevant resources towards raising awareness, reducing stigma, improving treatment and developing culturally appropriate dementia care services.